Mesenchymal stem cells as a promising cell source for integration in novel in vitro models - Afflerbach, Ann-Kristin; Kiri, Mark D.; Detinis, Tahir; Maoz, Ben M. (Biomolecules, 2020)
The human-relevance of an in vitro model is dependent on two main factors—(i) an appropriate human cell source and (ii) a modeling platform that recapitulates human in vivo conditions. Recent years have brought substantial advancements in both these aspects. In particular, mesenchymal stem cells (MSCs) have emerged as a promising cell source, as these cells can differentiate into multiple cell types, yet do not raise the ethical and practical concerns associated with other types of stem cells. In turn, advanced bioengineered in vitro models such as microfluidics, Organs-on-a-Chip, scaffolds, bioprinting and organoids are bringing researchers ever closer to mimicking complex in vivo environments, thereby overcoming some of the limitations of traditional 2D cell cultures. This review covers each of these advancements separately and discusses how the integration of MSCs into novel in vitro platforms may contribute enormously to clinical and fundamental research.
Gesehen am 24.11.2020